Anti‐viral therapy can be delayed or avoided in a significant proportion of HBeAg‐negative Caucasian patients in the Grey Zone. Issue 10 (25th March 2018) - Bonacci, M.; Lens, S.; Mariño, Z.; Londoño, M.‐C.; Rodríguez‐Tajes, S.; Mas, A.; García‐López, M.; Pérez‐del‐Pulgar, S.; Sánchez‐Tapias, J. M.; Forns, X.
Summary: Background: Grey Zone (GZ) is an ill‐defined situation including patients falling between inactive carrier (IC) state and HBeAg‐negative chronic hepatitis B (HBeAg‐negative CHB). Aims: To assess the long‐term outcomes of GZ patients compared to IC in the absence of treatment. Methods: Retrospective analysis of 287 IC and GZ HBeAg‐negative patients. Patients were classified into 4 groups at baseline: HBV‐DNA <2000 IU/mL and ALT <40 U/L (IC), HBV‐DNA <2000 IU/mL and ALT 40‐80 U/L (GZ‐1), HBV‐DNA 2000‐20 000 IU/mL and ALT <40 U/L (GZ‐2) or ALT 40‐80 U/L (GZ‐3). Data were also analysed using AASLD ALT criteria. Results: After a median follow‐up of 8.2 (5‐19) years, HBsAg loss occurred in about 15% ICs or GZ patients. Transition into IC state occurred in 40% of GZ patients. DNA fluctuations >2000 IU/mL correlated inversely with transition into IC and HBsAg loss. HBsAg levels were significantly lower in ICs than in GZ patients (338 IU/mL [20‐3269] vs 5763 IU/mL [2172‐17 754]; P  < 0.05). Among the latter group, there was an increasing gradient of HBsAg levels from GZ‐1 to GZ‐3 patients ( P  < 0.05). HBeAg‐negative CHB occurred in only 18 (6.3%) GZ patients. No patient developed cirrhosis nor advanced fibrosis. ALT/HBV‐DNA fluctuations and HBeAg‐negative CHB development were more frequent in genotype B/C patients, whereas HBsAg loss occurred only in genotype A/D patients. Conclusions: Most Caucasian GZ patients present excellent long‐term outcomes in the absence of treatment, with a high rate of HBsAg loss and low rate of progression to HBeAg‐negative CHB. HBV‐genotyping and HBsAg levels could help to predict outcomes and better classify GZ patients. Abstract : Linked Content This article is linked to Ridruejo paper. To view this article visithttps://doi.org/10.1111/apt.14644 .